Fotossíntese de proteção oxidativa em mudas de cajueiro expostas a uma atmosfera enriquecida com CO2 sob estresse salino. - Souza, Naiara Célida dos Santos de (2012)
The reduction of photosynthetic activity in plants under salt stress occurs due to the restriction of the influx of CO2 in the leaf mesophyll, caused in part by stomatal closure. Under these conditions, the reduction of the photosynthesis can lead to oxidative damage, which are assigned, mainly, the excessive production of hydrogen peroxide due to increased activity photorespiratory. Thus, the increase of CO2 pressure in the external environment may favor the influx in the mesophyll, favoring photosynthesis and attenuating the oxidative damage under salinity. In this sense, the present study was to evaluate the photosynthetic efficiency and oxidative damage in cashew plants grown under salinity when exposed to normal and elevated CO2. To this end, young seedlings (30 days after planting) were cultured in the absence (control) or presence of NaCl (100 mM NaCl) for eight days, in a greenhouse, and then were exposed to atmospheric pressure of CO2 (380 ppm) and elevated (760 ppm) in a growth chamber under controlled conditions, for seven days. The results show that cultivation at high pressures of CO2, in a short period, induced the initiation of a process of acclimation of cashew seedlings. This initial acclimation is associated with reduced rates of carbon assimilation and high carbohydrate contents. During cultivation saline, CO2 ambient, the seedlings showed typical responses to salt stress, with higher levels of TBARS, H2O2, higher Na + / K +, APX activity and induction of antioxidant non-enzymatic mechanism, as proline and anthocyanin. Whereas the culture in high CO2, reflected in conflicting responses, mainly related to oxidative changes. Seedlings subjected to a combination of salinity and high pressures of CO2 stimulated lipid peroxidation, non-photochemical dissipation (NPQ), the accumulation of amino acids, flavonoids and anthocyanins, higher cultivation in saline CO2 environment. On the other hand, have reduced the content of H2O2 and variables associated with photorespiration, as GO activity and content of glyoxylate. These results suggest that high pressures of CO2 induced damage additives to salinity, reflecting a complex interaction that was shown during an initial period of acclimation. In addition, the cashew to be a model native and contrasting, more studies are needed, especially be evaluating behavior over time, in a longer period.